Prospective Review of Mesenchymal Stem Cells Differentiation into Osteoblasts - Garg, Priyanka (Orthop Surg, 2017)
Stem cell research has been a popular topic in the past few decades. This review aims to discuss factors that help regulate, induce, and enhance mesenchymal stem cell (MSC) differentiation into osteoblasts for bone regeneration. The factors analyzed include bone morphogenic protein (BMP), transforming growth factor β (TGF‐β), stromal cell‐derived factor 1 (SDF‐1), insulin‐like growth factor type 1 (IGF‐1), histone demethylase JMJD3, cyclin dependent kinase 1 (CDK1), fucoidan, Runx2 transcription factor, and TAZ transcriptional coactivator. Methods promoting bone healing are also evaluated in this review that have shown promise in previous studies. Methods tested using animal models include low intensity pulsed ultrasound (LIPUS) with MSC, micro motion, AMD3100 injections, BMP delivery, MSC transplantation, tissue engineering utilizing scaffolds, anti‐IL‐20 monoclonal antibody, low dose photodynamic therapy, and bone marrow stromal cell transplants. Human clinical trial methods analyzed include osteoblast injections, bone marrow grafts, bone marrow and platelet rich plasma transplantation, tissue engineering using scaffolds, and recombinant human BMP‐2. These methods have been shown to promote and accelerate new bone formation. These various methods for enhanced bone regeneration have the potential to be used, following further research, in clinical practice.